Development Strategies for Tegalsambi Beach as a Community-Based Sustainable Tourism Destination in Tahunan District, Jepara Regency - Mohammad Ridlo; Edi Kurniawan (JPG (Jurnal Pendidikan Geografi), 2026)
Coastal tourism development in Indonesia faces increasing challenges in balancing economic growth, environmental sustainability, and community involvement. Tegalsambi Beach in Jepara Regency represents a coastal destination with significant natural and cultural potential, yet it requires strategic planning to ensure sustainable development. This study aims to analyze the development strategies of Tegalsambi Beach using the Sustainable Community-Based Tourism (SCBT) framework by examining stakeholder perceptions across six key dimensions: beach attractions, cultural attractions, amenities, accessibility, sustainability, and development constraints. A descriptive quantitative approach was employed through a survey of 100 respondents, consisting of tourists and local stakeholders. Data were collected using structured questionnaires and analyzed using descriptive statistics and SWOT analysis to identify internal and external strategic factors. The results indicate that Tegalsambi Beach possesses strong potential, particularly in its coastal landscape and the cultural value of the Perang Obor ritual, which serve as the main attractions of the destination. However, the findings also reveal that limited amenities, inadequate infrastructure, and weak institutional capacity remain critical constraints. The SWOT analysis further shows that while opportunities such as the growing trend of community-based tourism and government support are significant, challenges including environmental pressures and competition from nearby destinations must be addressed. In conclusion, the study demonstrates that sustainable development of Tegalsambi Beach requires integrated strategies focused on strengthening community institutions, improving basic facilities, enhancing environmental management, and optimizing culture-based tourism promotion. These findings confirm the relevance of the SCBT approach and provide practical recommendations for stakeholders in developing inclusive and sustainable coastal tourism destinations.Keywords: Sustainable tourism; Community-Based Tourism; Tegalsambi Beach; Jepara; SWOT.